Mathematical Analysis of an Eco-Epidemiological Model Incorporating Prey Refuge and Intraspecific Competition Among Predators - Pino Romero, Neisser (2025)
An eco-epidemiological model is discussed that extends the work of Lazaar and Serhani (2023) by including prey infection and recovery, refuge that predation, and competition among predators. The existence, uniqueness and positivity of the model solutions are proved, ensuring that they are bounded in the long run. The qualitative analysis identifies equilibrium points and stability conditions, while the Dulac-Bendixon criterion guarantees the absence of limit cycles. Numerical simulations prove the theoretical results and consequently, how disease, refuge and competition affect population dynamics and disease spread in ecosystems.